2018
DOI: 10.1186/s12909-018-1148-8
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone learning as an adjunct to vascular teaching – a pilot project

Abstract: BackgroundM-learning is education using personal mobile electronic devices. Given the prevalence of these in society and amongst healthcare professionals, we aimed to assess their use and feasibility in improving the educational programme of a single vascular institution.MethodsA weekly vascular departmental teaching programme was initiated with registrars giving 30-min presentations on a defined book chapter. Two multiple-choice questions (MCQ) per session were devised by a supervising consultant utilising th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…56 Teaching methods for trainees could include early patient contact/clinical experience, multimedia, and utilising smart phones for teaching. 57,58 These may be with virtual or real patientsboth are documented to promote meaningful theory learned using visual, audio, and verbal experiences and acquiring complex skills and knowledge. 58 Early clinical experience provides context to theoretical learning and improves understanding of how to apply new knowledge.…”
Section: Trainees and Studentsmentioning
confidence: 99%
“…56 Teaching methods for trainees could include early patient contact/clinical experience, multimedia, and utilising smart phones for teaching. 57,58 These may be with virtual or real patientsboth are documented to promote meaningful theory learned using visual, audio, and verbal experiences and acquiring complex skills and knowledge. 58 Early clinical experience provides context to theoretical learning and improves understanding of how to apply new knowledge.…”
Section: Trainees and Studentsmentioning
confidence: 99%
“…Mobile learning is widely practiced in universities as a sort of educational method (2, 8); however, the results of this study showed that some students do not respect the professional ethics associated with the use of mobile technology and find the cyber world a place to act beyond ethical limits.…”
Section: Discussionmentioning
confidence: 69%
“…Mobile devises have emerged as new learning tools with a notable potential both in classrooms and outdoor learning environments (1). Mobile learning (m-learning) refers to using mobile electronic devices for educational purposes (2). In short, it means using a mobile handheld electronic device for learning without time or place limitations (3, 4).…”
Section: Introductionmentioning
confidence: 99%
“…Correlation test results showed the statement of the use of mobile phones by students to learn, make the process of learning physics become efficient correlate 0.76 (moderate) with the belief that the use of mobile phones by students and teachers, strengthens and improves the quality of the learning process. This belief is supported by many research findings which state that mlearning strengthens and improves the quality of the learning process (Khan, Radzuan, Alkhunaizan, Mustafa, & Khan, 2019;Mughal, Atkins, Morrow, & Al-Jundi, 2018;Njenga, Oboko, Omwenga, & Maina, 2018).…”
Section: Resultsmentioning
confidence: 75%